Empowering Sustainable Development and Security through Computer Education and Technology Integration - Ibrahim, Umar (MultiTech Publisher, 2024)
This paper explores the pivotal role of computer education and technology integration in empowering sustainable development and security. The study employs a comprehensive literature review to establish the theoretical framework, identifying gaps in current knowledge. Utilizing a mixed-methods approach, we investigate the impact of technology on sustainable development and security outcomes. Empirical findings demonstrate the positive correlation between computer education, technological integration, and the enhancement of both sustainable development initiatives and security measures. The discussion delves into the implications of these results, emphasizing the potential for technology to catalyze positive change. Acknowledging challenges and limitations, the paper concludes with actionable recommendations for policymakers, educators, and practitioners seeking to leverage technology for societal advancement.